Regulation and Molecular Basis of Environmental Muropeptide Uptake and Utilization in Fastidious Oral Anaerobe Tannerella forsythia - Ruscitto, Angela; Honma, Kiyonobu; Veeramachineni, Vamsee M.; Nishikawa, Kiyoshi; Stafford, Graham P.; Sharma, Ashu (Frontiers in Microbiology, 2017)
Tannerella forsythia is a Gram-negative oral anaerobe associated with periodontitis. This bacterium is auxotrophic for the peptidoglycan amino sugar N-acetylmuramic (MurNAc) and likely relies on scavenging peptidoglycan fragments (muropeptides) released by cohabiting bacteria during their cell wall recycling. Many Gram-negative bacteria utilize an inner membrane permease, AmpG, to transport peptidoglycan fragments into their cytoplasm. In the T. forsythia genome, the Tanf_08365 ORF has been identified as a homolog of AmpG permease. In order to confirm the functionality of Tanf_08365, a reporter system in an E. coli host was generated that could detect AmpG-dependent accumulation of cytosolic muropeptides via a muropeptide-inducible -lactamase reporter gene. In trans complementation of this reporter strain with a Tanf_08365 containing plasmid caused significant induction of -lactamase activity compared to that with an empty plasmid control. These data indicated that Tanf_08365 acted as a functional muropeptide permease causing accumulation of muropeptides in E.coli and thus suggested that it is a permease involved in muropeptide scavenging in T. forsythia. Furthermore, we showed that the promoter regulating the expression of Tanf_08365 was activated significantly by a hybrid two-component system regulatory protein, GppX. We also showed that compared to the parental T. forsythia strain a mutant lacking GppX in which the expression of AmpG was reduced was significantly attenuated in utilizing free muropeptides. In summary, we have uncovered the mechanism by which this nutritionally fastidious microbe accesses released muropeptides in its environment, opening up the possibility of targeting this activity to reduce its numbers in periodontitis patients with potential benefits in the treatment of disease